2021
DOI: 10.1001/jamanetworkopen.2021.19929
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Breast Cancer Screening in a Safety-Net Hospital During the COVID-19 Pandemic

Abstract: National estimates project COVID-19 negatively influenced cancer screening, leading to an estimated deficit of 3.9 million breast cancer (BC) screenings among US adults. 1,2 In San Francisco, California, low-income neighborhoods disproportionately affected by COVID-19 bear the burden of higher BC stage at diagnosis. 3,4 We sought to evaluate the association of COVID-19 and BC screening in a safety-net hospital in San Francisco. MethodsThis cross-sectional study evaluated trends in BC screening at an urban int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 6 publications
3
58
1
4
Order By: Relevance
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in screening mammography rates were reported in all studies and ranged from 53.8% to 22.2% among registry-based studies 20 , 35 , 44 and 80.0% to 9.8% among non-registry-based studies. 18 , 24 , 25 , 31 , 34 , 36 , 39 , 41 , 43 , 49 Figure 2 displays the results of the meta-analysis of mammographic screening rate ratios. Overall, we noted that mammogram rates declined between 2019 and 2020 by 41% (RR: 0.59, 95% CI: 0.46–0.75) and 53% (RR: 0.47, 95% CI: 0.38–0.58) according to data derived from 3 registry-based and 10 non-registry-based studies respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Primary prevention is the main strategy to reduce the growing burden of colon, breast, and prostate cancer [ 37 ]. With regard to breast cancer alone, national estimates project that the COVID-19 pandemic is leading to an estimated deficit of 3.9 million breast cancer (BC) screenings among U.S. adults [ 38 ]. Unfortunately, the reduced rate of screening impacts cancer incidence, treatment, cancer-related mortality, and overall cost of cancer care long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that the proportion of completed mammograms was lowest among Black women at all time points. 14 Another study by Marcondes et al found no significant improvement or worsening of racial and ethnic disparities for any cancer screening after the hiatus was lifted. 15 Our data show similar findings and suggest a trend toward a mitigation of these disparities.…”
Section: Discussionmentioning
confidence: 97%